PENGARUH STRATEGI PEMBELAJARAN DAN KECERDASAN LOGIS MATEMATIS TERHADAP HASIL BELAJAR MATEMATIKA SEKOLAH DASAR KELAS VI - Moch. Sukardjo; Krisna Yusdiningtias (Jurnal Pendidikan Edutama, 2018)
Abstract: The accuracy in choosing a learning strategy is an important part in the effort to improve the achievement of student learning outcomes. Hence, this study aims to determine the effect of learning strategy and logical-mathematical intelligence as well as its interaction with mathematics learning outcomes.  This study used on experimental research by level 2 x 2 with 18 people were taken by simple random sampling in  Islamic Elementary School (SD Islam) Karya mukti. The result of this research found that there is an interaction effect between learning and logical-mathematical intelligence to match learning outcomes. Thus the selection of the relevant strategy, the acquisition of mathematics learning outcomes are influenced by the ability of the teacher to understand the characteristics of their students. The strategy applied to optimize the mathematics teacher of mathematics learning outcomes of students who have a logical-mathematical intelligence.Keywords : strategy, logical–mathematical intelligence, learning outcomes mathematicsAbstrak: Ketepatan dalam memilih strategi pembelajaran adalah bagian penting dalam upaya meningkatkan pencapaian hasil belajar siswa. Oleh karenanya penelitian ini bertujuan untuk mengetahui pengaruh strategi pembelajaran dan kecerdasam logis-matematis terhadap hasil belajar matematika. Penelitian ini menggunakan penelitian eksperimen rancangan treatment by level 2 x 2 dengan sampel 18 orang diambil secara simple random sampling di SD Islam karya mukti. Hasil penelitian ini menunjukkan bahwa ada pengaruh interaksi antara strategi pembelajaran dan kecerdasan logis matematis terhadap hasil belajar matematika. Sehingga pemilihan strategi pembelajaran yang sesuai dipengaruhi oleh kemampuan guru dalam memahami karakteristik siswanya. Strategi pembelajaran yang diterapkan guru dapat mengoptimalkan hasil belajar matematika siswa yang memiliki kecerdasan logis matematis yang berbeda-beda.Kata Kunci: strategi pembelajaran, kecerdasan logis matematis, hasil belajar matematika.